2020
DOI: 10.1002/oby.22832
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Feeding Time and Diet on Hepatic Steatosis and Gene Expression in Male Wistar Rats

Abstract: Objective Eating out of phase with the endogenous biological clock alters clock and metabolic gene expression in rodents and can induce obesity and type 2 diabetes mellitus. Diet composition can also affect clock gene expression. This study assessed the combined effect of diet composition and feeding time on (1) body composition, (2) energy balance, and (3) circadian expression of hepatic clock and metabolic genes. Methods Male Wistar rats were fed a chow or a free‐choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
2
10
1
Order By: Relevance
“…Thus, contrary to most mice studies, rats eating at the wrong time of day did not show an increased body weight, this could be due to the fact that in the current experiment the feeding period was only 10 h, instead of 12 h, or a stronger light‐induced inhibition of activity and feeding behavior during the light period in rats as compared to mice. In contrast, feeding efficiency was increased in the light‐fed animals and in previous experiments, we found increased adiposity in the light‐fed animals 37‐39 …”
Section: Resultscontrasting
confidence: 44%
See 1 more Smart Citation
“…Thus, contrary to most mice studies, rats eating at the wrong time of day did not show an increased body weight, this could be due to the fact that in the current experiment the feeding period was only 10 h, instead of 12 h, or a stronger light‐induced inhibition of activity and feeding behavior during the light period in rats as compared to mice. In contrast, feeding efficiency was increased in the light‐fed animals and in previous experiments, we found increased adiposity in the light‐fed animals 37‐39 …”
Section: Resultscontrasting
confidence: 44%
“…In contrast, feeding efficiency was increased in the light-fed animals and in previous experiments, we found increased adiposity in the light-fed animals. [37][38][39] A subset of animals was housed in metabolic cages, first under AL (baseline) feeding conditions and subsequently under TRF conditions (4 weeks) to assess physical activity and substrate metabolism. As expected, light-fed and dark-fed animals did not eat during the dark and light phases, respectively (Figure 1E).…”
Section: Physiological Parameters Display Altered Rhythms Upon Trfmentioning
confidence: 99%
“…Access to calories-rich food and time-restricted feeding are invariably associated with changes in circulating signals reflecting metabolic and behavioral adaptations [25]. In line with this, we observed that our BE model was associated with reduced circulating triglycerides and insulin, and increased circulating corticosterone during the anticipatory phase (Suppl.…”
Section: Time-locked Access To Palatable Diet Induces Adaptation Of Nutrients Partitioning and Metabolic Efficiencysupporting
confidence: 82%
“…Access to calories-rich food and time-restricted feeding are invariably associated with changes in circulating signals reflecting metabolic and behavioral adaptations (Oosterman et al, 2020). In line with this, we observed that our model of BE was associated with reduced circulating triglycerides (TG) and insulin and concomitant increase in circulating corticosterone during the anticipatory phase (Figure 2A-C) while overall insulin sensitivity, as assessed by oral glucose tolerance test, remained unchanged (Figure 2D, E).…”
Section: Time-locked Access To Palatable Diet Induces Adaptation Of N...supporting
confidence: 78%